Distinct episodic contexts enhance retrieval-based learning. Issue 9 (21st October 2018) - Schwoebel, John; Depperman, Acasia K.; Scott, Jessica L.
ABSTRACT: Spaced retrieval practice results in better long-term retention than massed retrieval practice. The episodic context account of this effect suggests that updated representations of the more distinct temporal contexts associated with spaced retrievals facilitate later recall. We examined whether environmental context, in addition to temporal context, may also play a role in retrieval-based learning. Participants studied and then attempted to retrieve the English translations of Swahili words during four acquisition blocks of trials. They were then randomly assigned to practice retrieving items three more times in one of the following conditions: massed practice with the same environmental context scene; massed practice with different environmental context scenes; spaced practice with the same environmental context scene; or spaced practice with different environmental context scenes. After a one-week delay, measures of recall, forgetting, and the joint probabilities between study session recall and final recall performance all indicated enhanced retention for both the spaced and different environmental context conditions. Indeed, after retrieving items in the study session, forgetting them during final recall was 371% more likely in the same context than in the different context conditions. These findings redefine and refine previous accounts of the episodic context model of retrieval-based learning.